Fine particulate matter aggravates smoking induced lung injury via NLRP3/caspase-1 pathway in COPD - Chiwook Chung; Suk Young Park; Jin-Young Huh; Na Hyun Kim; ChangHo Shon; Eun Yi Oh; Young-Jun Park; Seon-Jin Lee; Hwan-Cheol Kim; Sei Won Lee (BMC, 2024)
Abstract Background Exposure to noxious particles, including cigarette smoke and fine particulate matter (PM2.5), is a risk factor for chronic obstructive pulmonary disease (COPD) and promotes inflammation and cell death in the lungs. We investigated the combined effects of cigarette smoking and PM2.5 exposure in patients with COPD, mice, and human bronchial epithelial cells. Methods The relationship between PM2.5 exposure and clinical parameters was investigated in patients with COPD based on smoking status. Alveolar destruction, inflammatory cell infiltration, and pro-inflammatory cytokines were monitored in the smoking-exposed emphysema mouse model. To investigate the mechanisms, cell viability and death and pyroptosis-related changes in BEAS-2B cells were assessed following the exposure to cigarette smoke extract (CSE) and PM2.5. Results High levels of ambient PM2.5 were more strongly associated with high Saint George's respiratory questionnaire specific for COPD (SGRQ-C) scores in currently smoking patients with COPD. Combined exposure to cigarette smoke and PM2.5 increased mean linear intercept and TUNEL-positive cells in lung tissue, which was associated with increased inflammatory cell infiltration and inflammatory cytokine release in mice. Exposure to a combination of CSE and PM2.5 reduced cell viability and upregulated NLRP3, caspase-1, IL-1β, and IL-18 transcription in BEAS-2B cells. NLRP3 silencing with siRNA reduced pyroptosis and restored cell viability. Conclusions PM2.5 aggravates smoking-induced airway inflammation and cell death via pyroptosis. Clinically, PM2.5 deteriorates quality of life and may worsen prognosis in currently smoking patients with COPD. Graphical Abstract